2019
DOI: 10.4038/sljass.v9i1.7149
|View full text |Cite
|
Sign up to set email alerts
|

Waste Management in Sri Lanka: Challenges and Opportunities

Abstract: Most of the developing countries face the problem of managing waste properly. In 2012, cities world over, generated 1.3 billion tons of solid waste per year, amounting to a footprint of 1.2 kilograms per person, per day needless to state that with rapid population growth and urbanization, the municipal waste generation is expected to increase to 2.2 billion tons (MT) by 2025. Inadvertently, with the current trends continuing, it is likely to rise from 3.5 MTs to 6 MTs per day with, each person generating aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 4 publications
1
22
0
Order By: Relevance
“…Lord Buddha was the religious leader who practiced environmentally friendly lifestyle and inculcated those practices among his followers. However, Sri Lanka generates 8500MT of solid waste per day approximately and each person generates an average of 0.4 to 1 kg of waste per day (Dharmasiri, 2019). Waste collection and disposal responsibilities are assigned to the local authorities, Municipal Councils; Urban Councils and Pradeshiya Sabha.…”
Section: Global Waste Management Goalsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lord Buddha was the religious leader who practiced environmentally friendly lifestyle and inculcated those practices among his followers. However, Sri Lanka generates 8500MT of solid waste per day approximately and each person generates an average of 0.4 to 1 kg of waste per day (Dharmasiri, 2019). Waste collection and disposal responsibilities are assigned to the local authorities, Municipal Councils; Urban Councils and Pradeshiya Sabha.…”
Section: Global Waste Management Goalsmentioning
confidence: 99%
“…Many studies have examined the household waste disposal behavior with respect to waste management in developing and developed contexts and identified the factors (education; gender; age; social influence; household characteristics; living standards) affecting waste disposal behavior of households (Kumara and Pallegedara, 2020). Composition Surveys (WACS) conducted by the University of Peradeniya (2014), revealed that, nearly three fourth of total waste is generated from kitchens however, composting mechanism does not functioning in a proper manner (Dharmasiri, 2019). The collection of MSW in the country is very poor except in three main Municipal Councils; Colombo, Dehiwala-Mount Lavinia and Kotte which has about 50% collection value.…”
Section: Global Waste Management Goalsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, an open dumping site in Sri Lanka collapsed in 2016, revealing the short-sighted, unsustainable waste management strategies [2,3]. While most of the decisions in MSW management are driven by political and economic terms [4][5][6], waste composition, socio-economic, and environmental impacts are given limited attention during this process. Due to land scarcity factors, urban planning agencies became responsible for the ownership of waste disposal sites in Sri Lanka such that waste management was not only a matter of economics or environment, but also a spatial planning problem.…”
Section: Introductionmentioning
confidence: 99%